Changes in the expression of modulators of dentin mineralization by chronic exposure NaF - Gallará, Raquel Viviana (2015)
Fil: Gallará, Raquel Viviana. Universidad Nacional de Córdoba. Facultad de Odontología. Cátedra A de Química Biológica; Argentina.